An unusual presentation of dermatofibrosarcoma protuberans with pleomorphic sarcomatous transformation: potential pitfall and diagnostic strategy. (28th April 2016) - Cesinaro, Anna Maria; Mataca, Ema; Gambini, Claudio; Kutzner, Heinz
Abstract : Dermatofibrosarcoma protuberans (DFSP) is a low grade, superficial sarcoma characterized by a proliferation of monomorphous, spindle cells arranged in a storiform pattern and infiltrating the subcutaneous tissue. The tumor is typically CD34 positive, and shows the characteristic COL1A1‐PDGFB fusion gene, detectable either by florescent in situ hybridization (FISH) and polymerase chain reaction (PCR). We describe a case of DFSP with a focus of peculiar pleomorphic sarcomatous transformation. The focus constituted the entire bioptic tissue that was initially excised, raising considerable diagnostic problems for pathologist. The use of FISH as an ancillary technique allowed the right diagnosis.